Comparative Analysis of Perceptions of Doctors, Management, Nurses and Patients on the Use of the Enhanced Recovery After Caesarean Surgery Method Based on the Concept of Perceived Value - Tamon, Oktavian; Hasyim; Indrawati, Ratna; Erni, Nofi (GoAcademica Research & Publishing, 2024)
In this era of modernization, several companies, one of which is hospitals, are adopting E-Service Quality because currently patients prefer services that are quickly accessible wherever and whenever they are, so this adds to the main function of a service. One of the services of the Obstetrics and Gynecology unit, especially the delivery service using the ERACS (Enhanced Recovery After Caesarean Surgery) method, is a surgical procedure that increases profits for hospital Agencies. So, it can influence consumer value perceptions, perceived quality and hospital imAge and patient satisfaction. The aim of this research is to analyze differences in perceptions between the components of doctors, management, nurses and patients based on perceived value in implementing ERACS actions. This research method uses a quantitative research approach, survey method and the type of research is hypothesis testing with descriptive analysis and comparative analysis. The sampling technique used was a saturated sampling technique. The number of samples used was 50 respondents. The research results show that the Mann Whitney test analysis on the combination of all components which compares benefits and costs, shows that the p-value is 0.000 (p < 0.05), meaning there is a significant difference between benefits and costs on the combination of all components. It can be concluded that there is a significant difference between benefits and costs in the doctor, management, nurse and patient components.